Staffing Formation in the Hospitality Industry - Nikolskaya, Elena; Galkin, Dmitriy; Kovaleva, Natalia; Feoktistov, Sergei; Tretyak, Elena (Anais Brasileiros de Estudos Turísticos, 2022)
The authors aim to substantiate approaches to staff training in the hospitality industry. It is assumed that the management of the processes of prospecting, recruiting and hiring personnel, is the key to a company's success in the market of such a promising area such as the hotel industry. We identified that the personnel system of the hotel business in the Russian Federation is still in formation and requires significant efforts to coordinate the quantitative and qualitative levels of training of new specialists with the needs of hotel companies. It is evidenced in this study that the detailed analysis of the characteristics of the operation and personnel of the hotel industry, which will allow to determine the paths of development of the industry and make the transition to a higher level of development. It is found, therefore, that the most important task in solving the existing problems, in Human Resource Management in the tourism sector currently in Russia, is the search for new approaches to recruitment based on a modern concept of recruitment from contemporary management in modern enterprises.